Role of p97/VCP (Cdc48) in genome stability - Vaz, Bruno; Halder, Swagata; Ramadan, Kristijan (Frontiers in Genetics, 2013)
Ubiquitin-dependent molecular chaperone p97, also known as valosin-containing protein (VCP) or Cdc48, is an AAA ATPase involved in protein turnover and degradation. p97 converts its own ATPase hydrolysis into remodelling activity on a myriad of ubiquitinated substrates from different cellular locations and pathways. In this way p97 mediates extraction of targeted protein from cellular compartments or protein complexes. p97-dependent protein extraction from various cellular environments maintains cellular protein homeostasis. In recent years, p97-dependent protein extraction from chromatin has emerged as an essential evolutionarily conserved process for maintaining genome stability. Inactivation of p97 segregase activity leads to accumulation of ubiquitinated substrates on chromatin, consequently leading to protein-induced chromatin stress (PICHROS). PICHROS directly affects multiple DNA metabolic processes, including replication, damage responses, mitosis and transcription, leading to genotoxic stress and genome instability. By summarizing and critically evaluating recent data on p97 function in various chromatin-associated protein degradation (CAD) processes, we propose establishing p97 as a genome caretaker.